2011
DOI: 10.1007/s00402-011-1265-x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between alignments of upper and subaxial cervical spine: a radiological study

Abstract: There were negative correlations between C1-C2 angle and C2-C7 angle as well as between Oc-C2 angle and C2-C7 angle, and the former correlation was stronger. C1-C2 fixation angle was the key to regulate postoperative subaxial alignment in atlantoaxial arthrodesis. The optimal atlantoaxial fusion angle may be between 25° and 30°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 12 publications
7
45
1
Order By: Relevance
“…The Guo et al study also revealed slight differences with regard to sex and age in the occipitocervical alignment of healthy volunteers. 4 In our sample, age correlated only with C-7 SVA and C-7 slope, and differences between sexes were observed for C2-7 Cobb angle and C-7 slope only. However, the limited sample sized did not allow for further comparisons among age groups.…”
Section: Normal Values Sex and Age Differencescontrasting
confidence: 56%
See 4 more Smart Citations
“…The Guo et al study also revealed slight differences with regard to sex and age in the occipitocervical alignment of healthy volunteers. 4 In our sample, age correlated only with C-7 SVA and C-7 slope, and differences between sexes were observed for C2-7 Cobb angle and C-7 slope only. However, the limited sample sized did not allow for further comparisons among age groups.…”
Section: Normal Values Sex and Age Differencescontrasting
confidence: 56%
“…Previously, this effect was demonstrated for healthy persons only. 4 The negative correlation between the occipitocervical and subaxial spine could also be observed between C1-2 and C2-7, but the correlation coefficient was slightly smaller than that of the interdependence of Oc-C2 and C2-7. Guo et al 4 performed both measurements in asymptomatic healthy volunteers and found that C1-2 alignment correlated better with that of C2-7 than that of Oc-C2, but the differences they observed were small.…”
Section: Cervical Interdependencesmentioning
confidence: 87%
See 3 more Smart Citations